2016
DOI: 10.1007/s13244-016-0463-z
|View full text |Cite|
|
Sign up to set email alerts
|

Spectrum of MRI features of ganglion and synovial cysts

Abstract: Ganglion and synovial cysts occur mainly, but not necessarily, in association with osteoarthritis. Presentation varies widely, ranging from small, incidentally detected, asymptomatic lesions to giant ones that might be the source of symptoms, either due to their compressive effect on adjacent structures or due to complications, such as rupture. On magnetic resonance imaging they are typically presented as smooth, well-circumscribed, thin-walled, unilocular, and homogeneously T2-hyperintense lesions. An identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…SC and GC are frequent benign cystic lesions occurring in various bodily joints. They are usually associated with degenerative joint disease, rheumatoid arthritis, trauma and tumors [3,4]. Angelini A, et al have analyzed previous reported cases of anterior SC and GC of the hip and showed that out of 39 reported cases, 44 % had no comorbidities while 31% had rheumatoid arthritis, 23% had osteoarthritis and 2% had hip contractures [3].…”
Section: Cystic Lesions Of the Hip Jointmentioning
confidence: 99%
See 1 more Smart Citation
“…SC and GC are frequent benign cystic lesions occurring in various bodily joints. They are usually associated with degenerative joint disease, rheumatoid arthritis, trauma and tumors [3,4]. Angelini A, et al have analyzed previous reported cases of anterior SC and GC of the hip and showed that out of 39 reported cases, 44 % had no comorbidities while 31% had rheumatoid arthritis, 23% had osteoarthritis and 2% had hip contractures [3].…”
Section: Cystic Lesions Of the Hip Jointmentioning
confidence: 99%
“…Indeed, the knee is the most common joint followed by the hip where SC is more common than GC. GC occurs primarily in the wrist arising most commonly from the dorsal aspect of the scapholunate ligament followed by the radioscaphoidscapholunated interval, the scaphotrapezial, or the metacarpotrapezial joints [4]. Paralabral cysts (PC) are common cystic lesions in the hip joint and are associated with an intraarticular hip pathology, in particular labral tears [5].…”
Section: Cystic Lesions Of the Hip Jointmentioning
confidence: 99%
“…Lack of a true endothelial lining constitutes the differentiating feature from synovial cysts [18]. Ganglion cysts can arise from the joint capsule, ligaments, tendon sheaths, bursae or subchondral bone [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Usually, no solid/enhancing components are seen; although, occasionally, internal T2 hypointense debris or even osseous loose bodies can be seen [19]. Erosion/invasion of adjacent bone may be present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation